Harnessing Opportunities for Productivity Enhancement for Sorghum & Millets (HOPE): Baseline Survey, Uganda - Mwema, Catherine; Orr, Alastair; Namazi, Stella; Ongora, Dennis (2017)
A survey was conducted in 2015 to provide baseline information for HOPE project activities for finger millet in Uganda. The sample comprised 94 treatment and 96 control households from Serere and Lira districts. The majority of treatment households (52%) had adopted improved varieties of finger millet in the main season (March-July), compared to just 10% of households in the control group. Farmers’ top three trait preferences were for high yield, early maturity/drought resistance, and marketability. About 60% of finger millet production was sold. Farmers’ top three perceived constraints on finger millet related to marketing, including low prices, price fluctuations, and high transport costs. Decisions about crop sales and use of income from the sale of finger millet were not made exclusively by men but mostly shared. About one-third of households in the treatment group had participated in project activities and received small seed packs. Gross margin analysis showed that, on a full-cost basis, improved varieties were profitable (UGX 130,000 /acre) while local varieties were unprofitable (UGX - 530 /acre). On a cash-cost basis the gross margin for improved varieties (UGX 240,402/acre) was three times higher than for local varieties (UGX 9,223 /acre).